GLOBAL PROBLEMS - Toyeva Gulchiroy To'lqinjon qizi (TADQIQOTLAR, 2025)
This article discusses the most pressing global issues in the modern world, their causes, and consequences. Problems such as climate change, environmental degradation, poverty, hunger, wars, pandemics, and human rights violations pose serious threats to all of humanity. Addressing these challenges requires international cooperation, sustainable development policies, and increased environmental awareness.